Pathomorphological features of the skin and muscle tissue of experimental animals in the case of lifetime and postmortem damage - A. V. Kis (Patologìâ)
The problem of forensic medical diagnosis of tissue injury is currently the subject of numerous investigations. Pathomorphological changes of the skin and muscle tissue of experimental animals, resulting in the case of lifetime and postmortem traumatic injuries, depending on the time and temperature, were revealed by the author. Data obtained by the author is very necessary for improving the forensic medical diagnosis of traumatic soft tissue injuries.